An analysis of the mobile library of St. Luke's Medical Center in Quezon City - Putong, Francis John D. (2003)
The St. Luke's Medical Center, one of the most advanced health institutions in the country to date, has lived to its trademark of pioneering in programs for the benefit of their patient clientele. With this, they started their mobile library service on August of 2000. It was with the purpose of presenting comprehensive information about the present state of this in-house mobile library, and determining its effectivity, that this thesis was undertaken. It is also sought to recommend solutions to the problems faced by bookmobiles as an approach to contributing knowledge to different user groups.